1982
DOI: 10.1002/bip.360210206
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of glucomannan

Abstract: SynopsisFive different glucomannan samples were recrystallized from dilute solution. Depending on the experimental conditions, the crystals obtained could be identified as corresponding to the mannan I (anhydrous precipitate of more or less regular lozenge-shaped crystals) or mannan I1 (hydrated gel-forming pseudo-fibrillar precipitate). High-molecular-weight material, low temperature of crystallization, or a polar crystallization medium favored the mannan I1 polymorph, whereas a low-molecular weight, a high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 19 publications
4
38
0
Order By: Relevance
“…(c) The presence of slightly branched Man residues in fraction K4p would also contribute to the insolubility of this material. Glucomannans can crystallize on to cellulose [36], and may be expected to form an insoluble complex with the less branched xyloglucans. (d) The presence of significant amounts of 4-linked Xyl residues in and the absence of branched Xyl residues from fractions KIA and K3A suggest that a proportion of these residues may form integral parts of the xyloglucans.…”
Section: Glycosidic-linkage Analysis Of Koh-soluble Fractionsmentioning
confidence: 99%
“…(c) The presence of slightly branched Man residues in fraction K4p would also contribute to the insolubility of this material. Glucomannans can crystallize on to cellulose [36], and may be expected to form an insoluble complex with the less branched xyloglucans. (d) The presence of significant amounts of 4-linked Xyl residues in and the absence of branched Xyl residues from fractions KIA and K3A suggest that a proportion of these residues may form integral parts of the xyloglucans.…”
Section: Glycosidic-linkage Analysis Of Koh-soluble Fractionsmentioning
confidence: 99%
“…It was shown that with mannan and glucomannan polymers, the mannan I structure was obtained more easily with low molecular weight material, whereas mannan II corresponded to higher molecular weight (4,8). A close resemblance exists thus between the crystallization of cellulose IV^ and mannan I as with both polymers, the crystallization phenomena appear to be directed by related parameters.…”
Section: Discussionmentioning
confidence: 82%
“…This is in particular described in the case of mannan and glucomannan polymers (4,8) where crystals of mannan I are usually obtained with low degree of polymerization (DP) material, whereas only mannan II is found when higher DP are recrystallized.…”
mentioning
confidence: 94%
“…The properties of this gel were reviewed by Okimasu et al (1). There have been, however, very few data on the morphological characteristics of the gel (2,3). We have studied the liquid crystalline behaviors of cellulosic materials and reported about the crosslinked hydroxypropyl cellulose (HPC) films retaining cholesteric liquid crystalline order (4).…”
Section: Introductionmentioning
confidence: 99%
“…When konjac mannan is blended with HPC, the resultant material is expected to exhibit some novel properties. Konjac mannan is known to have an affinity to cellulose (2) or xanthan (5).…”
Section: Introductionmentioning
confidence: 99%